Evaluating the effectiveness of MOOCs in developing agribusiness pitching skills: a study of agropreneurship diploma students / Jacqueline Joseph - Joseph, Jacqueline (Penerbit UiTM (UiTM Press), 2025)
This study explores the effectiveness of Massive Open Online Courses (MOOCs) in developing pitching skills for agribusiness students. Pitching skills are critical for agropreneurship students as they seek to secure funding, partnerships, and market access. The study focuses on 27 fourth-semester diploma students in agropreneurship who completed a 4-week MOOC designed to improve business pitching. A mixed-methods approach was used, including pre-and post-course assessments to measure changes in students’ confidence and skill comprehension and focus group discussions to gather detailed feedback. Quantitative findings show a significant increase in confidence and understanding of crucial pitching concepts following the course. Qualitative feedback highlights that students valued the accessibility and flexibility of the MOOC but expressed a need for more interactive exercises to better develop practical pitching skills. The study suggests that MOOCs can effectively support specific skill-building in agropreneurship but should incorporate hands-on elements to enhance real-world application. These results offer insights into the role of online courses in niche skill development and provide recommendations for future MOOC design in agribusiness education.